The logic of identity and copy for computational artefacts. (26th March 2018) - Angius, Nicola; Primiero, Giuseppe
Abstract: Defining identity for entities is a long-standing logical problem in philosophy, and it has resurfaced in current investigations within the philosophy of technology. The problem has not yet been explored for the philosophy of information and of computer science in particular. This paper provides a logical analysis of identity and copy for computational artefacts. Identity is here understood as the relation holding between an instance of a computational artefact and itself. By contrast, the copy relation holds between two distinct computational artefacts. We distinguish among exact, inexact and approximate copies. We use process algebra to provide suitable formal definitions of these relations, using in particular the notion of bisimulation to define identity and exact copies, and simulation for inexact and approximate copies. Equivalence is unproblematic for identical computational artefacts at each individual time and for inexact copies; we will examine to which extent the formal constraints on identity criteria discussed in the literature are satisfied by our approach. As for inexact and approximate copy, they are intended as a weakening of the identity relation in that equivalence and other constraints on identity are violated. The proposed approach also suggests a computable treatment of identity and copy checking.